Revisiting the Visual Acuity Curves. A Proposed Methodology for the Evaluation of Postoperative Visual Acuity in Presbyopia - Labiris G; Bakirtzis M; Panagis C; Mitsi C; Vorgiazidou E; Konstantinidis A; Delibasis KK (Clinical Ophthalmology)
Georgios Labiris,1 Minas Bakirtzis,1 Christos Panagis,1 Christina Mitsi,1 Eleftheria Vorgiazidou,2,3 Aristeidis Konstantinidis,1 Konstantinos K Delibasis2 1Department of Ophthalmology, University Hospital of Alexandroupolis, Alexandroupolis, Greece; 2Department of Computer Science and Biomedical Informatics, University of Thessaly, Lamia, Greece; 3School of Medicine, Aristotle University of Thessaloniki, Thessaloniki, GreeceCorrespondence: Georgios Labiris, Department of Ophthalmology, University Hospital of Alexandroupolis, Dragana, Alexandroupolis, 68100, Greece, Tel +30 2551030990, Email labiris@usa.netPurpose: To identify the minimally required number of distances of visual acuity (VA) measurements for the reliable estimation of the visual acuity curve (VAC) and area of the curve (AoC) in presbyopia correction.Patients and Methods: The study was divided into a validation and a clinical phase with a total recruitment of 120 participants (120 eyes) who underwent uncomplicated pseudophakic presbyopia surgery with bilateral premium intraocular lenses (IOL) implantation. This study was conducted in the Department of Ophthalmology, University Hospital of Alexandroupolis, Alexandroupolis, Greece. Postoperative VAC and AoC were calculated with VA measurements taken at nine pre-defined distances. A mathematical model based on cubic spline interpolation was developed and assessed comparing the VAC and AoC values obtained using nine distances, with the ones predicted when a subset of VA measurements was inserted into the model.Results: Less than four measurements resulted in unreliable VAC and AoC assessment. Optimal distances for four to six VA measurements were determined. Mean error in the prediction of VAC and AoC of the clinical group ranged from 2.54 Letters/1.74% (6 measurements) to 2.90 letters/2.9% (4 measurements), respectively.Conclusion: Mathematical models that use cubic spline interpolation provide reliable VAC and AoC estimation, even with four VA measurements, when obtained at specific distances.Keywords: presbyopia, premium IOLs, visual acuity curve, area of the curve, DDART